2021
DOI: 10.1200/jco.2021.39.15_suppl.e19542
|View full text |Cite
|
Sign up to set email alerts
|

Same-day pegfilgrastim or pegfilgrastim-cbqv prophylaxis in miniCHOP chemotherapy based regimens for non-Hodgkin lymphoma.

Abstract: e19542 Background: Non-Hodgkin’s lymphoma, specifically, diffuse large B-cell lymphoma (DLBCL) is most frequently diagnosed among older patients. The utilization of a reduced dose of cyclophosphamide, doxorubicin, vincristine, and prednisone (miniCHOP) chemotherapy-based regimen has an improved tolerance and toxicity profile in select patient populations. Prophylaxis with pegfilgrastim or its biosimilar pegfilgrastim-cbqv is administration on the same day of chemotherapy in all patients with MiniCHOP at The U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, another recent systematic review with meta-analysis showed a significantly higher FN rate in patients administered same-day prophylaxis compared with those receiving next-day prophylaxis both in the first cycle (odds ratio [OR] = 2.56, 95% CI, 1.19–5.48, p = 0.02) and across all cycles (OR = 1.54, 95% CI, 1.29–1.84, p < 0.00001) [ 32 ]. At the 2021 American Society of Clinical Oncology (ASCO) Annual Meeting, 3 small (< 120 patients) retrospective analyses evaluated same-day administration of prefilled syringe all studies showed increased rates of FN with same-day administration [ 33 35 ]. Pegfilgrastim, when used as indicated, decreases chemotherapy-induced FN.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another recent systematic review with meta-analysis showed a significantly higher FN rate in patients administered same-day prophylaxis compared with those receiving next-day prophylaxis both in the first cycle (odds ratio [OR] = 2.56, 95% CI, 1.19–5.48, p = 0.02) and across all cycles (OR = 1.54, 95% CI, 1.29–1.84, p < 0.00001) [ 32 ]. At the 2021 American Society of Clinical Oncology (ASCO) Annual Meeting, 3 small (< 120 patients) retrospective analyses evaluated same-day administration of prefilled syringe all studies showed increased rates of FN with same-day administration [ 33 35 ]. Pegfilgrastim, when used as indicated, decreases chemotherapy-induced FN.…”
Section: Discussionmentioning
confidence: 99%
“…Observational ( Athar et al, 2007 ; Bartels et al, 2021 ; Bilen et al, 2017 ; Billingsley et al, 2015 ; Cheng et al, 2014 ; Eckstrom et al, 2019 ; Gupta et al, 2007 ; Hoffmann, 2005 ; Ibrahim et al, 2011 ; Karol et al, 2013 ; Kumar et al, 2009 ; Lokich, 2005 ; Lokich, 2006 ; Matera et al, 2017 ; McBride et al, 2021 ; Micha et al, 2013 ; Schuman et al, 2009 ; Skarlos et al, 2009 ; Vance & Carpenter, 2006 ; Weycker et al, 2017 ; Whitworth et al, 2009 ; Woods et al, 2010 ) and randomized studies ( Burris et al, 2010 ; Siefker-Radtke et al, 2016 ) have evaluated the extent of prophylaxis provided by a single dose of pegfilgrastim administered within the first 24 hours after completion of chemotherapy. Here, we present a meta-analysis of studies comparing the efficacy of same-day pegfilgrastim to the standard protocol of administration > 24 hours following completion of chemotherapy (next-day).…”
mentioning
confidence: 99%